Configurações das capacidades dinâmicas em diferentes fases do ciclo de vida organizacional: um estudo multicaso no setor hoteleiro - Hattore, Jéssica Ramirez (2021)
New technologies, the Industry 4.0 revolution, and the advent of the collaborative economy have brought about significant changes in the hospitality industry. Airbnb is considered the big disruptor for traditional hosting. Another challenge faced by the sector is the impacts arising from the Covid-19 pandemic. To face these challenges, it is essential that companies develop Dynamic Capabilities to be better prepared for environmental changes throughout their organizational life cycle. Dynamic Capabilities evolve over time and are combined by the company's unique characteristics, which make them distinct from others and thus create a barrier to imitation. Thus, the general objective of the research was to investigate what are the Dynamic Capabilities that determine an organizational performance that allows a company to remain in the market for the long term, in the hotel sector. The theoretical framework of this dissertation was based on the themes of Dynamic Capabilities theory, organizational life cycle, lodging facilities and Settings Approach. Literature searches were carried out in order to identify in the Service Administration literature the skills, resources and competences that can be considered as “Dynamic Capabilities”. Literature findings revealed 16 Dynamic Capabilities that were grouped into dimensions. Subsequently, the analysis conditions for the configurations were elaborated, in order to explain the attributes of each Dynamic Capacity, which were later analyzed to identify patterns and form generalizations. The research has a descriptive character and is characterized as a study of multiple cases, with cross-sectional analysis. Data were collected through documents and semi-structured interviews with the managers of three organizations in the hotel sector in Foz do Iguaçu. The QCA principles were applied as a technique, as a configurational comparative analysis. As results revealed 12 configurations of Dynamic Capabilities that were commonly important for the companies under study, namely: Capability of entrepreneurial orientation; Capacities of knowledge, experience and skills of employees; Networking capabilities; Detection, seizure and reconfiguration capabilities; Capacity of organizational ambidexterity; Capacities to manage performance; Ability to understand customer needs; Capacities to manage organizational knowledge; Capabilities related to learning mechanisms, routines and practices; Capabilities related to operational agility; Ability to manage processes; and Ability to manage ICT tools. The configurations ofthe Dynamic Capabilities generated are the capabilities that are always present and are decisive for superior performance. The results also revealed that two of the three organizations studied develop Dynamic Capabilities, which helps them remain long-lived in the sector in which they operate. Suggestions are presented to professionals, and theoretical-methodological suggestions for future research.